SOCIO-ANTHROPOLOGIE DES PRATIQUES FONCIÈRES DES KYAMAN D’ABIDJAN (CÔTE D’IVOIRE) - Adou Paul Venance (European Scientific Journal, ESJ, 2015)
The construction of Abidjan as economic capital of Ivory Coast to engender a transformation of the land practices of the autochthons (Kyaman). The urbanization has severely disrupted the customary space of the Kyaman so that the commodification prevailed over the conservatism in the management of the local lands. The socio-anthropological analysis of the land practices Kyaman emphasizes the social orders and their transformation the justification of the link between the urbanization and the corruption of the community land system.